Acoustic levitation for sensitive material handling - Kwok, Hao Jun (2015)
Levitation is a process which an object is suspended in a stable position against gravity, without any mechanical support or physical contact. Levitation can be actualized by various means, such as electrostatic force, aerodynamic force, magnetic force, acoustic radiation force and so on. For this project, an acoustic radiation force is used prove that it can levitate a CD-ROM. In waffle transportation, it is not advisable to use clamp or other holding devices to transport a waffle from one location to another as it might contaminate the waffle or even damage it. Many methods have being experimented to levitate a thin silicon waffle so as to prevent contamination on the waffle. Such methods are electromagnetic force and ultrasonic acoustic levitation force. Electromagnetic force has its limitation as not all waffles are magnetic. Thus electromagnetic force is being rule out as a choice for waffle handling.